2020
DOI: 10.1136/annrheumdis-2020-217309
|View full text |Cite
|
Sign up to set email alerts
|

Normal human enthesis harbours conventional CD4+ and CD8+ T cells with regulatory features and inducible IL-17A and TNF expression

Abstract: BackgroundThe human enthesis conventional T cells are poorly characterised.ObjectivesTo study the biology of the conventional T cells in human enthesis.MethodsCD4+ and CD8+ T cells were investigated in 25 enthesis samples using immunofluorescence, cytometrically, bulk RNAseq and quantitative real-time PCR following anti-CD3/CD28 bead stimulation to determine interleukin (IL)-17A and tumour necrosis factor (TNF) levels. T-cell receptor (TCR) repertoires were characterised and a search for putative T-cell reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 43 publications
(43 reference statements)
1
44
0
1
Order By: Relevance
“…Whether HLA-B27 could be mediating IEL activation in patients with SpA, and whether it is possible for these cells to home to the inflamed joints of these patients, is interesting to speculate. Relevant to this point, recent studies have revealed the presence of resident-like CD8 + T cells in axial spinal ligaments 134 , whereas other studies have demonstrated high frequencies of granzyme-producing CD8 + T cells with gut-related homing markers, in the peripheral joints of SpA patients 123,135 .…”
Section: Immunological Alterations In Spamentioning
confidence: 99%
“…Whether HLA-B27 could be mediating IEL activation in patients with SpA, and whether it is possible for these cells to home to the inflamed joints of these patients, is interesting to speculate. Relevant to this point, recent studies have revealed the presence of resident-like CD8 + T cells in axial spinal ligaments 134 , whereas other studies have demonstrated high frequencies of granzyme-producing CD8 + T cells with gut-related homing markers, in the peripheral joints of SpA patients 123,135 .…”
Section: Immunological Alterations In Spamentioning
confidence: 99%
“…Additionally, human iliac crest MSCs and MSCs from murine femurs display enhanced osteogenic differentiation after exposure to either IL-17A or TNF [15,16], supporting the rationale for IL-17A being potentially involved in aberrant bone reactions in AS. Normal murine and human spinal entheses also have tissue resident innate and adaptive immune cells capable of either IL-17A and TNF production, depending on the system and conditions, which points towards the proximity of immune cells and cytokines that could enhance or fine tune tissue repair responses for neighboring MSCs [17][18][19][20]. Indeed, stromal cells from AS patients and a healthy facet capsule reported enhanced osteogenic potential of the AS patient-derived cells, with IL-17A also driving increased osteogenesis from these same cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the work by Watad et al, 1 which the authors demonstrated the characterisation of enthesisresident T cells and their corresponding cytokine responses upon stimulation. This commendable work mimicked enthesitis-involved inflammatory pathogenesis of spondyloarthritis, for instance, psoriatic arthritis (PsA).…”
mentioning
confidence: 99%
“…This commendable work mimicked enthesitis-involved inflammatory pathogenesis of spondyloarthritis, for instance, psoriatic arthritis (PsA). Particularly, the authors proposed that entheseal T cells may secrete interleukin (IL)-17 and much more tumour necrosis factor α (TNF-α) in response to anti-CD3 and anti-CD28 (as suggested in figure 3 by Watad et al 1 ); furthermore, phosphodiesterase 4 (PDE4) inhibitors suppressed the expression of the above mentioned inflammatory cytokines (as suggested in figure 5 by Watad et al 1 ). As PDE4 inhibitors have been used to treat autoimmune diseases and advanced malignancies, 2 we are highly interested in whether infliximab, a neutralised antibody for TNF-α and a widely prescribed biologic disease-modifying antirheumatic drugs for a number of autoimmune diseases, would as well modulate the immunity of entheseal or synovial T cells in patients with PsA in clinical settings.…”
mentioning
confidence: 99%